Analysis of Islamic Worldview Content in Maskoeri Jasin's Basic Natural Science Textbooks : Analisis worldview Islam dalam buku teks Ilmu Alamiah Dasar karya Maskoeri Jasin - Subagiya, Bahrum; Sauri, Sofyan; R, M. Dahlan; Handrianto, Budi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
This study aims to analyze Maskoeri Jasin's Basic Natural Science textbook based on the Islamic worldview. The background of this research is the lack of Basic Natural Science textbooks that integrate science concepts with the Islamic worldview. A holistic and integrated understanding of Basic Natural Science, including the influence of Islamic values and worldview, is essential in developing better attitudes and knowledge in students. This research uses a qualitative approach with a content analysis method. The results of this study conclude that the Basic Natural Science textbook by Maskoeri Jasin contains several Islamic worldviews in his book. The Islamic worldview in the book includes the concept of God, science, nature and man. The concepts of the Islamic worldview need to be clarified and reinforced firmly, so further efforts need to be made to improve and strengthen the concepts of the Islamic Worldview in the book. This effort will provide significant benefits in developing scientific understanding based on Islamic principles and fulfilling educational needs that uphold academic and spiritual integrity.